Relationship of Chest Girth, Body Length, and Sex with Body Weight and Average Daily Gain in Batur Lambs - Aisyah, Imas; Setyaningrum, Agustinah; Susanto, Agus (Faculty of Agriculture, 2024)
This study aimed to investigate the relationships between chest girth, body length, and sex with body weight and average daily gain (ADG) in Batur lambs. The study sample consisted of 12 male and 8 female Batur lambs, aged 5 to 12 months, with an average body weight of 23.97 kg. Data were collected through a survey study using a random sampling method. The variables measured included chest girth, body length, sex, body weight, and ADG. The results demonstrated that: (1) the regression equation for chest girth on body weight was Y= -50.47 + 1.02CG (r = 0.91, R2 = 0.82); (2) the regression equation for body length on body weight was Y= -64.19 + 1.58BL (r = 0.88, R2 = 0.78); (3) the multiple regression equation for chest girth and body length on body weight was Y = -62.08 + 0.65CG + 0.69BL (r = 0.93, R2 = 0.85). These results indicate a very strong positive correlation between chest girth, body length, and body weight, suggesting that body weight in Batur lambs can be accurately predicted using these variables. However, ADG was not significantly correlated with chest girth or body length due to a low coefficient of determination.